Case Report: Post-operative mitral valve replacement complicating with a large cardiac mass and the role of TEE in Imaging [version 2; peer review: 2 approved] - Deepa Noronha; Chaithra Nayak; Syed Waleem Pasha; Padmanabh Kamath; Narasimha Pai D (F1000Research)
Background Postoperative complications are an integral part of valve surgery. Common complications include hematomas, bleeding, valve dehiscence, paravalvular leak, and acute PV thrombosis. With the available data from published articles, the rate of all valve-related complications is 0.7 to 3.5% per patient annually. [1] The pathology involved is multifactorial, often blood vessel injury leading to bleeding and hematoma. Although postoperative complications are evident, incidental diagnosis of a cardiac mass in an asymptomatic and hemodynamically stable patient postoperatively is crucial, requiring non-invasive imaging for immediate surgical action. Case presentation A woman in her 50s presented with chief complaints of worsening dyspnoea with suddenonset and chest pain. Clinical findings showed apex shifted downward and outward, wide split S2, and a mid systolic murmur radiating to the mid axillary line. Twelve-lead ECG showed LA enlargement, that aligned with X-ray findings. 2D Echocardiography revealed MVP with severe MR and a dilated LV. The patient underwent successful mitral valve replacement as per ACC/AHA class I recommendation. However, postoperative TTE showed a remarkably large mass measuring 5.6 cm*4.6 cm in the RA. Reexploration was performed, followed by mass excision. Plenty of organized clots were seen compressing the RA. TEE showed no evidence of mass. Following stabilization,the patient was discharged considering optimal INR values and prosthetic valve function assessed by echocardiography. The patient’s symptoms improved during the first follow-up. Conclusion Although postoperative cardiac complications are common, appropriate diagnosis with TTE and TEE has benefited surgeons. TEE-guided reexploration aids surgeons in decision-making and strategic approaches. Failure to diagnose such complications in asymptomatic patients can ultimately complicate the procedure. Henceforth, sonographers must be skilled in the detection and identification of unusual complications to guide redo interventions. Such an approach minimizes mortality, redo procedures, and avoids CPB hence reducing long-term prognosis and outcomes with valve replacement.